Indium–gallium–zinc–oxide thin-film transistors: Materials, devices, and applications - Zhu, Ying; He, Yongli; Jiang, Shanshan; Zhu, Li; Chen, Chunsheng; Wan, Qing (Journal of semiconductors, 2021)
Since the invention of amorphous indium–gallium–zinc–oxide (IGZO) based thin-film transistors (TFTs) by Hideo Hosono in 2004, investigations on the topic of IGZO TFTs have been rapidly expanded thanks to their high electrical performance, large-area uniformity, and low processing temperature. This article reviews the recent progress and major trends in the field of IGZO-based TFTs. After a brief introduction of the history of IGZO and the main advantages of IGZO-based TFTs, an overview of IGZO materials and IGZO-based TFTs is given. In this part, IGZO material electron travelling orbitals and deposition methods are introduced, and the specific device structures and electrical performance are also presented. Afterwards, the recent advances of IGZO-based TFT applications are summarized, including flat panel display drivers, novel sensors, and emerging neuromorphic systems. In particular, the realization of flexible electronic systems is discussed. The last part of this review consists of the conclusions and gives an outlook over the field with a prediction for the future.